Penegakan Hukum Terhadap Pelaku Penjualan Kosmetik Illegal Secara Online Oleh Balai Besar Pengawas Obat Dan Makanan (BPOM) Pekanbaru - Fitrah Zaki Amri; Mukhlis R; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Online trading activity or what is called E-commerce is a transaction activity that uses electronic media as a means of connecting between business people and consumers, so that agreements or agreements that are created are through online. One example of items that are widely traded online is cosmetics. Cosmetic circulation is an activity or series of activities aimed at transferring hands, spreading cosmetics. So the right to circulate cosmetics is only certain people who already have a permit and criminal for those who distribute illegal cosmetics online without any permission based on Article 197 of Law No. 36 of 2009 concerning Health.Violations of illegal cosmetics sales sold online occurred in the 2017-2019 time span in Riau Province as many as 39 cases, this proves that there is urgency about the circulation of illegal cosmetics that circulate online in Riau Provision. Information on the illegal distribution of illegal cosmetics without online marketing authorization is obtained from public reports and / or BPOM Pekanbaru conducts surveys directly by monitoring both online through cyber patrols with takedown links and offline (Stores / sellers' houses operate). In this case BPOM Pekanbaru has the authority to conduct a search, seizure, crime scene, summons, examination, arrest and detention. BPOM Pekanbaru conducts law enforcement in the enforcement of online cosmetic product distribution practices in Riau Province, by coordinating with the PPNS / Police Korwas, Attorney's Office, District Court, Health Office, Satpol PP.The obstacle for the Pekanbaru Center for Drug and Food Control (BPOM) in enforcing criminal law against illegal cosmetics sellers without an online marketing permit is the lack of public awareness of the cosmetics content and the dangers to health, inadequate budgetary funds and inadequate human resources. . Efforts are being made to overcome obstacles in law enforcement of criminal acts against the sale of illegal cosmetics online without marketing authorization by the Pekanbaru Center for Drug and Food Control (BPOM) Pekanbaru is to optimize Law Enforcement, Strengthen and improve synergy through cooperation with stakeholders or other criminal justice systems, Collaborating with IdEA (Indonesian E-Comerce Association), Collaborating with cargo transportation services, Collaborating with the Ministry of Communication and Information and Socialization and counseling to the publicKeywords: Cosmetics, Online, Illegal, Without Circular Permit